Rising damp in historical buildings: A Venetian perspective. (March 2018) - Falchi, Laura; Slanzi, Debora; Balliana, Eleonora; Driussi, Guido; Zendri, Elisabetta
Abstract: Considering several real case studies, moisture distribution due to rising damp in Venetian brick masonries is discussed and empirical models are developed. Moisture content and soluble salt data of 25 historical buildings in Venice are analysed. Data are scrutinized using statistical methods, obtaining contour plots and estimating the validity of linear and non-linear models. The models confirm that masonries are usually soaked with water till 120–150 cm over sea level, while the evaporation zone ranges in height from 200 cm to 350 cm. In the perpendicular section, moisture distribution depends on several contingent factors such as, among them, the proximity and the exposition of the external façades to the water action. Highlights: Moisture content and soluble salts data of 25 buildings in Venice were collected. Moisture distributions due to rising damp in venetian masonries is discussed. Linear modelling for rising damp are developed. Non-linear regression trees of the moisture data were implemented. Statistic relevance of height, depth, and location on moisture content distribution.